Асимптотические свойства эмпирических оценок параметров марковских последовательностей - Вовк, Л.Б.; Касицкая, Е.И.; Самосёнок, А.С. (Кибернетика и системный анализ, 2012)
Розглянуто умови, при яких можлива апроксимація критеріальної функції марковського процесу з єдиною точкою мінімуму її емпіричною оцінкою. Доведено теореми про збіжність наближених оцінок як для випадку скінечнної множини станів марковського процесу, так і для ипадку компактної множини. The authors consider the conditions under which the criterion function of the Markov process with a unique minimum point can be approximated by its empirical estimate. Theorems about the convergence of the empirical function to the original one in some probabilistic sense are established for both finite and compact sets of states of the Markov process.